Enhanced Electrocatalysis of the Oxygen Reduction Reaction Using Cobalt and Iron Porphyrin/Ionic Liquid Systems - Aguirre-Quintana, M; Aguirre-Quintana, M (Wiley-VCH Verlag, 2019)
Oxygen reduction reaction mediated by electrodes composed of graphite powder, octylpyridinium hexafluorophosphate as a binder, and cobalt and iron metal octaethylporphyrins is studied. Morphological and composition changes of the electrodic surfaces are observed employing the ionic liquid (IL) as a binder by scanning electron microscopy along with X-ray microanalysis. Cyclic voltammetry and electrochemical impedance spectroscopy studies indicate that both the ILs and porphyrins are capable of generating an electrocatalytic effect in terms of current and/or potential toward this reaction, as well as increasing the conductive ability of the systems, presenting a synergistic effect between the ILs and the porphyrins. Scan rate studies determine that with the mixing of Co–Fe porphyrins, an oxygen reduction close to four electrons, either directly or through the production of a hydrogen peroxide intermediate, is generated. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim